PHOTODEGRADATION OF METHYLENE BLUE DYE USING TiO2/ZnO/CoO NANOCOMPOSITE PHOTOCATALYST - IRNAMERIA ( NIM: 20514024 ), DIRA
Nanoparticle materials have been an interest for many researchers because the nanomaterial can be designed to show a novelty in material and to enhance the physical and chemical properties from the material significantly. One of the material that has been synthesized in nano size was metal oxide nanoparticle, and mostly the researchers have researched metal oxide TiO2 and ZnO. Both of the metal oxide (TiO2 and ZnO) are photocatalyst material that have good photocatalytic activity to decrease pollutant in water, such as dyes, pesticides, and detergents. Although TiO2 and ZnO have good photocatalytic activity, but their photocatalytic reactions mostly take place in ultraviolet range and cause the limitation of using TiO2 and ZnO in the treatment of pollutan in water. It is important to synthesize a TiO2 – ZnO composite photocatalyst doped with an element which can cause the composite to be irradiated under visible light or sunlight. This research has been successful to synthesize a TiO2/ZnO/CoO nanocomposite material using chemical precipitation method based on sol-gel. The precursors used in this research are zinc acetate dihydrate Zn(CH3COO)2.2H2O, cobalt acetate tetrahydrate Co(CH3COO)2.4H2O and titanium (IV) ethoxide. The characterizations of nanocomposite are done with XRD for crystal structure analysis, FTIR to observe the functional group, SEM- EDS and TEM for morphology analysis, and UV-DRS for energy of band gap analysis. The XRD analysis shows that nanocomposite has peaks similar with TiO2 (JCPDS 21-1276), ZnO (JCPDS 36-1451) dan CoO (JCPDS 42-1300). This result show that nanocomposite consists of metal oxides TiO2, ZnO and CoO. IR analysis from the nanocomposite material shows a spesific peak from ZnO at wave number range 418.55 cm-1 dan 526.57 cm-1. SEM image shows that the nanocomposite which is inhomogenous and there are agglomerations on several nanocomposite surfaces. TEM analysis shows that the nanocomposite has the particle size about 38.46 – 130.77 nm. UV-DRS analysis shows that the nanocomposite has a 2.75 eV of band gap energy. The performance of the nanocomposite material is observed with photodegradation of methylene blue dye and learns about the effect of pH, irradiation time and nanocomposite mass for photodegradation of methylene blue dye. Concentration of methylene blue used in this research is 4 ppm. The results show that the synthesized nanocomposite can be used in photodegradation of methylene blue dye. Optimal condition from photodegradation process are pH 7, irradiation time 210 minutes and mass of nanocomposite 0.04 grams. The percentage of degradation of methylene blue dye at pH 7 and irradiation time of 210 minutes is 71.05%. The kinetics of photocatalytic degradation are observed with comparation from the degradation processes in three conditions , which are photolysis using UV lamp, photolysis using neon lamp, and degradation without irradiation, in the same condition of pH, irradiation and degradation time, and mass of nanocomposite. According to these three conditions, the maximum percentages of degradation achieved are 71.05% for photolysis using UV lamp, 62.18% for photolysis using neon lamp, and 63.08% for degradation without irradiation. The kinetic of photocatalytic degradation follows the kinetic of degradation pseudo one order and the number of rate constant kTZCo under irradiation UV lamp is 0.004 minute-1 , kTZCo under irradiation neon lamp is 0.002 minute-1, kTZCo at degradation without irradiation is 0.004 minute-1. For comparison purposes, the kinetic of photocatalytic degradation follows the kinetic of degradation pseudo one order and the number of rate constant kTZCo is 0.002 minute-1 and the number of rate constant kTiO2/ZnO is 0.009 minute-1.